Not in the African Image: Utopia, Dystopia and the Politics of Destitution in the Fiction of Dambudzo Marechera. - Pordzik, Ralph (Spaces of Utopia, 2012)
The article addresses the utopian dimension at work in the fiction of Zimbabwean writer Dambudzo Marechera, taking into account the concepts of destitution and interculturality. It analyzes the organizing conceptual image of black sunlight in Marechera's novel "Black Sunlight" to clarify instances of creative parasitic communication. It explores the parasitic ecriture in "The Black Insider," one of narrative precursors of "Black Sunlight," and considers the parasite as postcolonial utopist.